Real-world evidence for immunotherapy in the first line setting in small cell lung cancer. (October 2022) - Sagie, Shira; Maixner, Nitzan; Stemmer, Amos; Lobachov, Anastasiya; Bar, Jair; Urban, Damien
Highlights: Two immune-checkpoint inhibitors have recently been approved for first-line treatment in ES-SCLC. Real-world data on the efficacy of ICIs in a heterogeneous patient population is scarce. We demonstrate the efficacy of ICIs in patients of poor PS and advanced disease, not represented in RCTs. ICIs are significantly beneficial after adjustment for baseline clinical parameters. Abstract: Objective: Despite major progress over the past decade in the field of lung cancer care, only mild advances have occurred in Small Cell Lung Cancer (SCLC), with prognosis remaining poor. Based on two randomized clinical trials (RCTs), two checkpoint-inhibitors have recently been approved in extensive-SCLC with moderate improvements in median overall survival (OS). However, only limited data exist regarding the impact of immunotherapy in real-world SCLC patients. This study reports the efficacy of immunotherapy in the first-line treatment of extensive-stage SCLC patients in a real-world setting. Methods: a retrospective cohort study of all patients treated for extensive-SCLC with chemotherapy with or without immunotherapy, at a single center in Israel between October-2017 and July-2021. Patient characteristics, adverse-events and survival analyses were conducted. Results: Of 102 patients identified, 54 patients (53%) received immunotherapy in addition to chemotherapy. 34.7% of patients had a performance status (PS) of 2–4. Patients that received only chemotherapy were older, had more liver metastasis and a poorer PS. In the whole cohort, patients receiving immunotherapy had a significantly longer median OS (353 days vs 194 days, HR = 0.40p < 0.0001). After stratification by PS groups, survival analysis remained significantly longer in the PS 0–1 group (HR 0.43, p = 0.0036), with a trend for better survival in the PS 2–3 group. Multivariate analysis validated an OS advantage with immunotherapy (HR = 0.46, p = 0.004). Conclusion: We present evidence for the efficacy of immunotherapy in SCLC in a real-world setting. Although treatment groups differ in their baseline characteristics, it appears that even some patients not included in RCTs, such as poor PS, may benefit from the addition of immunotherapy to their treatment protocol.